TAHLILUL MAWAD DIRASIYAH FI KITABI TA'LIMI AL LUGHAH AL ARABIYAH - Adib Muhammad 'Ulwan (Jurnal Al-Maqoyis, 2019)
The teaching of the Arabic language had a great development from its experts from all sides in Indonesia, in strategy, method and method, even the vertical books that teachers used in education. before using the textbook. There must be analyzed and observed first. Is the book suitable for education or was not fit. Because many of the teachers complain about the problems they faced in education, the causes of which are the textbooks in which the subjects were not appropriate and in conformity with the rules of teaching the Arabic language. Therefore, the researcher would like to analyze the contents of this book in order to know whether the book is worth using in education or is it not suitable for teaching. This study aims to analyze the study materials in the book "Teaching the Arabic Language for Secondary Schools" in order to know whether the materials included in this book are appropriate to the Arabic educational rules. Or was it not appropriate to the correct educational rules in the Arabic language? The researcher uses the qualitative descriptive method in the library method.